Thoracoscopy and talc pleurodesis for malignant pleural effusions - Beatriz Romero; Ana Pardessus (Barcelona Respiratory Network Reviews)
Malignant pleural effusion (MPE) is the result of the direct infiltration of the pleura by neoplastic cells and affects more than 15% of cancer patients. The incidence of this type of effusion is increasing in parallel with the rising incidence of cancer, with patients experiencing an increasing survival rate due to diagnostic and therapeutic advances. This article aims to review two fundamental aspects of the diagnostic and therapeutic management of MPE: medical thoracoscopy as a fundamental tool for the direct exploration of the pleural cavity, and pleurodesis with talc to achieve adhesion of the two pleural layers, thereby preventing re-accumulation of fluid and reducing the symptoms in these patients.